Exploring the Interplay between Habits of Mind and Problem-Solving Skills in Online Mathematics Learning: Insights from Three-Variable Linear Equation Contextual Problems - Rahmatya Nurmeidina; Nafisa Nur Zaqiyah; Arif Ganda Nugroho; Andini Andini; Nuqthy Faiziyah; Mazlini Binti Adnan; Ahmad Syar’i (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
This research aims to analyze students' problem solving ability in linear equations of three variables contextual problem solving in the terms of habits of mind of students at class X MA Muhammadiyah 2 Al-Furqan in contextual problem solving in online learning. This research is a qualitative research with descriptive method. The researchers used  problem-solving ability test and  habits of mind questionnaire as well as in-depth interviews with research subjects as data collection method. The subjects of this research were 3 students of class X IPA MA Muhammadiyah 2 Al-Furqan who came from high, medium, and low ability groups. These students participated in mathematics learning using blended learning.  The results showed that the problem solving ability and habit of mind were interrelated and support each other.  Students with high habits of mind have high problem solving ability, students with medium habits of mind have medium problem solving ability, and students with low habits of mind have low problem solving ability. Students' problem solving ability is high on the indicator of understanding the problem and low on the indicators of making plans and implementing plans. Students' habits of mind are classified as moderate to high on the indicator of perseverance or never giving up, and moderate to low on the indicator of enthusiasm in responding and the indicator of daring to take responsibility and face risks. The main finding of this study confirms that effective problem solving skills require good habits of mind.  The research result shows the importance of developing positive thinking habits in learning  mathematics can improve students' problem-solving skills. Thus, the integration of online learning with approaches that pay attention to aspects of habits of mind can be an effective strategy in improving students' mathematics achievement.